HAKIKAT PERDAGANGAN DALAM HADIS BUKHARI MUSLIM: Keywords: Nature, Trade, Hadith, Bukhari, Muslim. - Hadi, Nur (Program Studi Muamalah Fakultas Syariah dan Hukum, 2023)
Abstract The word tijarah is mentioned 8 times in seven letters, namely al-Baqarah: 16 and 282, al-Nisa ': 29, al-Taubah: 24, al-Nur: 37, Fathir: 29, Shaf: 10 and al-Jum' ah: 11. While the word bai'a (sell) is referred to as 4 times, Al-Baqarah: 254 and 275, Ibrahim: 31 and Al-Jum'ah: 9. The word al-Syira is in 25 verses. Two verses include the connotation of trade in the actual business context, namely Joseph 21-22. Then what is the nature of trade according to the hadith of the Messenger of Allah in saheeh Bukhari Muslim. Then the results of the study can be concluded that in the book of Mausu'ah al-Hadith al-Nabawiyah, from the Bukhari and Muslim hadith perceptions of the nature of trade there are nine traditions, eight from Bukhari (No. 115, 439, 884, 1917, 1922, 2074, 4519 , 6807) and one from Muslim (206). The nature of trade is to learn to fulfill the mandate, learn to live life by always seeking sustenance that is lawful and good (not usury), so that it must learn religion and teach it, so that it does not neglect the remembrance of Allah for all its blessings, truly grateful is better than world trade and trade, the nature of trade is trade and commerce with God Almighty..